2010
DOI: 10.3109/03093646.2010.501512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AFO Design on Walking after Stroke

Abstract: This study was conducted to compare the effects of three ankle-foot orthosis (AFO) designs on walking after stroke and determine whether an ankle plantar flexion contracture impacts response to the AFOs. A total of 30 individuals, ranging from 6-215 months post-stroke, were tested in four conditions: shoes only (SH), dorsi-assist/dorsi-stop AFO (DA-DS), plantar stop/free dorsiflexion AFO (PS), and rigid AFO (Rigid). Kinematics, kinetics, and electromyographic (EMG) activity were recorded from the hemiparetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 26 publications
7
82
0
1
Order By: Relevance
“…Stroke patients are commonly accompanied by ankle plantarflexion contracture due to spasticity of the calf muscle and tibialis anterior weakness (Mulroy et al 2010). As was observed in a previous study (Tinazzi et al 2005), TENS stimulation of calf muscles in this study changed the excitability of brain cortical areas, or rather reciprocal inhibition and facilitation that enabled efficient movement and increased balance function was observed.…”
Section: Discussionsupporting
confidence: 65%
“…Stroke patients are commonly accompanied by ankle plantarflexion contracture due to spasticity of the calf muscle and tibialis anterior weakness (Mulroy et al 2010). As was observed in a previous study (Tinazzi et al 2005), TENS stimulation of calf muscles in this study changed the excitability of brain cortical areas, or rather reciprocal inhibition and facilitation that enabled efficient movement and increased balance function was observed.…”
Section: Discussionsupporting
confidence: 65%
“…7,13 Hesse et al 7 investigated electromyography (EMG) of the TA muscle and recorded a decrease in activation when individuals post stroke walked with a rigid AFO compared to walking without an AFO. Mulroy et al 14 found that a plantarflexion stop AFO reduces TA muscle activity in patients post stroke; however, they also demonstrated that a rigid AFO and a dorsiflexion assist/dorsiflexion stop (DA/DS) AFO did not reduce TA muscle activity. 14 The DA/DS orthosis was hinged with elastic bands to provide dorsiflexion assistance during swing and a posterior strap to limit dorsiflexion to five degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Mulroy et al 14 found that a plantarflexion stop AFO reduces TA muscle activity in patients post stroke; however, they also demonstrated that a rigid AFO and a dorsiflexion assist/dorsiflexion stop (DA/DS) AFO did not reduce TA muscle activity. 14 The DA/DS orthosis was hinged with elastic bands to provide dorsiflexion assistance during swing and a posterior strap to limit dorsiflexion to five degrees.…”
Section: Introductionmentioning
confidence: 99%
“…The current modern design of AFOs includes articulated devices capable of assisting plantar lexion during stance. Whereas some studies con irmed the bene its of assistive AFOs [12,13], other studies demonstrated a minimal effect of traditional AFOs on global gait kinematics in hemiplegic patients [14]. For this reason, taken into consideration the economic cost and the bulkiness of some articulated AFOs, often the clinical attitude is to use standard rigid model in the daily rehabilitation practices.…”
Section: Introductionmentioning
confidence: 99%